Some Properties of Certain Multivalent Analytic Functions Involving the Cătas Operator - E. A. Elrifai; H. E. Darwish; A. R. Ahmed (International Journal of Mathematics and Mathematical Sciences)
We introduce a certain subclass of multivalent analytic functions by making use of the principle of subordination between these functions and Cătas operator. Such results as subordination and superordination properties, convolution properties, inclusion relationships, distortion theorems, inequality properties, and sufficient conditions for multivalent starlikeness are provide. The results presented here would provide extensions of those given in earlier works. Several other new results are also obtained.